Hubungan Motivasi Berprestasi dengan Academic Flow Siswa - Rafly Tidar; Isti’adah, Feida Noorlaila; Nugraha, Agung (JAMBURA Guidance and Counseling Journal, 2024)
This study aims to determine the relationship between achievement motivation and academic flow in students of SMK Negeri 2 Tasikmalaya. Achievement motivation serves as a driving force that spurs students to strive for desired success and excel in competitive situations. While the concept of flow provides important support for student learning. This study uses a quantitative approach with correlational methods. The subjects of this study were SMK Negeri 2 students in grades X, XI, and XII totaling 330 students. The sampling technique used was probability sampling technique in the form of Simple Random Sampling. The research hypothesis test used the Pearson Product Moment correlation technique with the help of the SPSS 27.0 for windows program. The results showed: (1) in general, the achievement motivation of students of SMK Negeri 2 Tasikmalaya is in the High category by 72% in the score of 54-72, (2) in general, the academic flow of students of SMK Negeri 2 Tasikmalaya is in the Moderate category by 75% in the score of 45-66, (3) correlation analysis obtained a correlation coefficient rxy = 0.619 (significance 0.000 <0.05) which means that the researcher's hypothesis is accepted, namely there is a positive relationship between achievement motivation and academic flow in students of SMK Negeri 2 Tasikmalaya.